Figurative Language in Little Bee by Chris Cleave: A Stylistic Analysis - MAALOUL, Ibtihaj; BOUSBIA, Metira (University of Eloued جامعة الوادي, 2024)
Figurative language plays a crucial role in shaping meaning and emotional resonance in literature. Chris Cleave’s powerful novel Little Bee utilizes a rich tapestry of figurative language to explore themes of displacement, trauma, and cultural differences. This dissertation delves into a stylistic analysis of the novel, examining how Cleave employs figures of speech to show what effects they have in constructing meaning and a compelling narrative. While previous studies on Little Bee focused on thematic contents or postcolonial issues, a stylistic analysis of Cleave’s use of figurative language remains unexplored. This dissertation aims to bridge this gap by analyzing how similes, metaphors, and other figures of speech contribute to the power of Little Bee. The study follows Leech and Short’s stylistic analysis in analyzing the figurative language; a close reading approach is employed to identify and analyze various figures of speech used by the author, as well as the corpus analysis, in addition to secondary data sources such as online books, academic journals, etc. The analysis shows that similes and metaphors are the most used in comparison to other figures of speech like personification, hyperbole…, etc. In addition, figures of speech are mostly used by Little Bee: metaphors, personification, repetition, hyperbole, imagery, alliteration, onomatopoeia, rhetorical questions, and idioms to show marginalization, hybridity, and displacement, while Sarah mostly uses: similes, symbolism, allusion, oxymoron, and idioms to express her complex emotions. Figurative language plays an important role in reflecting characters’ origins, both Nigerian and British. تلعب اللغة المجازية دورًا حاسمًا في تشكيل المعنى والصدى العاطفي في الأدب. تستخدم رواية كريس كليف ذات المعنى القوي "النحلة الصغيرة" نسيجًا غنيًا من البلاغة لاستكشاف موضوعات النزوح والصدمات والاختلافات الثقافية. تتعمق هذه المذكرة في التحليل الأسلوبي للرواية، وتدرس كيفية استخدام كليف للصور البيانية لإظهار التأثيرات التي تحدثها في بناء المعنى والسرد المقنع. بينما توجد دراسات نقدية للرواية، في حين أنّ الدراسات السابقة لنحلة الصغيرة متعلقة بمواضيع ما بعد الاستعمار، لا يزال التحليل الأسلوبي لاستخدام كليف للبلاغة غير مستكشف. تهدف هذه المذكرة إلى سد هذه الفجوة من خلال تحليل كيفية مساهمة التشبيهات والاستعارات والصور البيانية الأخرى في قوة سرد الرواية. تتبع الدراسة التحليل الأسلوبي في تحليل اللغة المجازية؛ كما يتم استخدام منهج القراءة الدقيقة لتحديد وتحليل مختلف الصور البيانية التي يستخدمها المؤلف، واعتماد التحليل الأسلوبي ل" ليتش و شورت" لتحليل البلاغة، بالإضافة إلى مصادر البيانات الثانوية مثل الكتب على الإنترنت والمجلات الأكاديمية وما إلى ذلك. يُظهر التحليل أن التشبيهات والاستعارات هي الأكثر استخدامًا مقارنة بالصور البيانية الأخرى مثل التجسيد والمبالغة...، إلخ. بالإضافة إلى ذلك، يتم استخدام صور بيانية في الغالب من قبل شخصية النحلة الصغيرة: الاستعارات، والتجسيد، والتكرار، والمبالغة، والصور، والجناس الاستهلالي، والمحاكات الصوتية، والأسئلة البلاغية، والعبارات الاصطلاحية لإظهار الإزاحة والصدمة، بينما تستخدم سارة في الغالب: التشبيهات، والرمزية، والتلميح، والتناقض في اللغة، والعبارات الاصطلاحية للتعبير عن مشاعرها المعقدة. تلعب اللغة المجازية دورًا مهمًا في عكس أصول الشخصيات، النيجيرية والبريطانية.
Literature and Civilization
Keywords: Figurative Language; Little Bee; Postcolonial Literature; Stylistic Analysis.; البلاغة، النحلة الصغيرة، أدب ما بعد الاستعمار، التحليل الأسلوبي.